(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses word meanings in speech, the function of context in the resolution of polysemy in the text, and the significance of word meaning and its investigation. The significance of polysemy phenomena in the language system, their application in the language, and the significance of the language are all considered in the graduation qualifying work, and appropriate solutions have been discovered. The issues of polysemy, various techniques to studying it, the structure and actual usage of polysemic words, in particular.